Proses Pendampingan Produk dan Kemasan Keripik Pisang HN IKM Desa Sukareja - Agus Yudianto; Meddy Nurpratama; Nana Supriatna Sonjaya; Taufansyah Firdaus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
The community service program in Sukareja Village, Balongan District, Indramayu Regency aimed to enhance the local community's economic skills through banana chip production training. Conducted over two days, the activities included socialization, hands-on training in banana processing, packaging, and basic product marketing. The results showed improved participant skills and a positive shift in entrepreneurial attitudes, along with the formation of a banana chip-based business group. Challenges included limited production equipment and short training duration. Going forward, further training in digital marketing and product quality improvement is needed to expand market reach and enhance the competitiveness of local products.